Uslub Dialogis Kisah Nabi Musa As. Dalam al-Qur’an - Yuli Irsyadul Ibad (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2020)
The Qur'an was revealed by Allah Swt. to the Prophet Muhammad Saw. in a very fluent language, Arabic with all its amazing characteristics. in the story of the Qur'an we find many verses that are dialogues between Allah Swt. and His messengers, between the apostles and his people, between pious people and others. And this conversation has a profound impact on the speaker as well as on the listener. In the revelation of God that the Qur'an there are many perfect stories, among the stories of the Qur'an ‎ which is very amazing and filled with mystery is the story and dialogue between the Prophet Moses with his people, the Prophet Moses with God, the Prophet Moses with Prophet Khidir and others. With the Balaghah Science approach, we can find that the words and dialogue of the Apostles can be used as guidelines and role models for us when communicating thoughts, ideas, intentions, feelings, and emotions directly in the world of education or for society. On this occasion the author will only examine the dialogue in the story of the Prophet Moses contained in the Qur'an ‎ with the aim to be more focused and not too long discussion. There is also a Balaghah qualitative research that specializes in Ma'ani knowledge, more precisely about Ijaz and Ithnab, with the hope of obtaining in-depth and detailed results. After the author conducted research on Ijaz and Ithnab in the conversation on the story of Moses in the Qur'an, the writer got several results, including that in the Qur'an there are 22 ijaz, 13 for ijaz qashr and 9 for ijazhadzfu. And there are 33 for ithnab, namely 3 for al-Idhahba'dal ibham (explanation after the unclear ones), 2 for dzikrul khas ba’dal ‘am(mentioning those that are specific after the general nature), 5 for tadzyil , 6 for takmil, 1 for tatmim, 5 for i'tiradh and 8 for tikrar. In the ijaz and ithnab there are many secrets, deep meanings, and enormous value. The purpose of ijaz and ithnab is to summarize, glorify, glorify, praise, criticize, strengthen meaning, explain meanings and others.